Implementasi Pemanfaatan Teh Bunga Telang (Clitoria Ternatea) Sebagai Solusi Herbal Dalam Manajemen Hipertensi Dan Gula Darah - Sari Rahmadhani; Nurdina Putri; Rahmi Amini; Dewi Gulyla Hari; Khazanah Nurain Nurdin; Putri Tri Hartini (Universitas Mataram, 2026)
This community service program aimed to enhance community knowledge and skills in utilizing butterfly pea flower tea (Clitoria ternatea) as a supportive herbal approach for hypertension management and blood glucose control. The activity was conducted using an educational and applicative approach through the delivery of health-related materials and a demonstration of the proper and hygienic preparation of butterfly pea flower tea for the target community. The implementation method comprised preparation, execution, and evaluation stages, with improvements in participants’ knowledge assessed through pre-test and post-test questionnaires, as well as observations of participant engagement throughout the activity. The results indicated an increase in community understanding regarding the benefits, processing methods, and consumption of butterfly pea flower tea as a complementary therapy. Overall, this program contributed positively to community empowerment through the utilization of safe, affordable, and locally available herbal plants, with potential benefits in supporting the prevention and management of non-communicable diseases, particularly hypertension and blood glucose disorders.